A Cohort Analysis of Patients with Stage I Twin-to-Twin Transfusion Syndrome from a Major Referral Hospital in Northern China. Issue 2 (15th October 2019) - Yang, Jing; Yuan, Peng-Bo; Wei, Yuan; Li, Hong-Tian; Wang, Xue-Ju; Li, Lu-Yao; Jiang, Yuan-Hui; Wang, Jing; Gong, Xiao-Li; Zhao, Yang-Yu
Abstract: Objective: To describe the outcomes of Stage I twin-to-twin transfusion syndrome among patients treated with expectant management (EM), amnioreduction (AR), or fetoscopic laser occlusion of chorioangiopagous vessels (FLOC). Methods: A cohort of 89 cases was studied. Based on the initial management strategy, patients were classified into three groups: the EM, AR, and FLOC. We assessed perinatal survival to 28 days of age and categorized pregnancy outcomes as good (twin live birth at ≥30.0 weeks), mixed (single fetal demise or delivery between 26.0 and 29.9 weeks), or poor (double fetal demise or delivery at <26.0 weeks). Results: 26 (29.2%) patients underwent EM, 35 (39.3%) underwent AR, and 28 (31.5%) underwent FLOC therapy. Of those managed expectantly, 19.2% experienced spontaneous abortion, 50% progressed in stage, and 30.8% remained stable or regressed. After adjusting for potential confounders including maternal age, nulliparity, placenta location, and recipient maximum vertical pocket, and so on, FLOC therapy and AR were associated with significantly [odds ratio ( OR ) = 0.09] and borderline significantly ( OR = 0.20) reduced risks of poor pregnancy outcomes and of no survivors to 28 days of age after birth ( OR = 0.04 and OR = 0.20, respectively) compared with EM. Conclusion: About 70% of those treated with EM progressed in stage or experienced fetal loss. Compared to EM, intervention may decrease the risk of poor pregnancy outcomes and improve the perinatal survival rate.